Implementation Of CERDIK Behavior In The Elderly At The Graha Resident Senior Karya Kasih Medan - Martini, Sri; Pandiangan, Angelika; Novitarum, Lilis; Pane, Jagentar; Ice Saragih (Jurnal EduHealth, 2024)
CERDIK behavior is an action that implements clean and healthy living behavior to prevent and reduce the risk of degenerative diseases. This research aims to identify the application and behavior of CERDIK towards the elderly at Graha Resident Senior Karya Kasih Medan. The type of research design is survey research with a population of 70 elderly people. The sampling technique in this research is purposive sampling with a sample size of 40 people. The results of the research show that the implementation of CERDIK behavior towards the elderly at the Graha Resident Senior Karya Kasih Medan 56.1% had good CERDIK behavior. It is hoped that health workers at Graha Resident Senior Karya Kasih Medan will pay more attention to improving the health of the elderly by actively assisting the elderly and implementing CERDIK behavior on a regular basis.